Intersections at the Border: Immigration Enforcement, Reproductive Oppression, and the Policing of Latina Bodies in the Rio Grande Valley - Gomez, Madeline M. (Columbia Journal of Gender and Law, 2015)
A series of events in 2014 brought significant attention to the United States-Mexico border. Over the summer, reports of an influx of undocumented Central American immigrants began circulating.[2] Though most coverage mentioned only children crossing the border, many of these young migrants traveled alongside their mothers. Reports of this influx raised public awareness about the increased level of immigration enforcement at the border and the rise of federal family detention centers in south Texas. That same year, a series of lawsuits against the State of Texas’s House Bill 2, which implemented significant restrictions on reproductive health clinics and abortion services in the state, shone a light on the health crisis facing women in the Rio Grande Valley. Part I of this paper lays out the constituent systems of immigration enforcement and anti-abortion policies in recent Texas history and situates these systems within larger national trends. Part II addresses the way the systems work together, using a framework of “intersectional subordination” to highlight the particular violence they work upon undocumented immigrant Latina women and Latino/a communities more broadly. Part III gives a brief historical perspective on the intersectional failure of the Chicano/a rights and reproductive rights movements. It argues that the marginalization of Latina women, generally, and activism against Latina reproductive oppression specifically, has contributed to the development of an abortion jurisprudence that fails to remedy the expansive negative outcomes of anti-abortion policies. Finally, Part IV concludes by arguing that the undue burden standard fails to protect marginalized women from violations of their reproductive and bodily rights and argues for reworking abortion jurisprudence and reproductive justice advocacy to better encompass the full intersectional experience and racialized outcomes of anti-abortion policies.